2020
DOI: 10.5005/jp-journals-10071-23443
|View full text |Cite
|
Sign up to set email alerts
|

Personal Protective Equipment: A Pandora's Box

Abstract: Countries all over the world writhing under the wrath of coronavirus face not only the challenge of protecting their population but the tougher challenge of protecting their healthcare workers (HCWs) dealing with the patient population. This pandemic has put unprecedented pressure on global healthcare systems, with personal protective equipment (PPE) being the most notable one. Apart from the challenge of procurement of PPE, the major challenge is rationalizing the use of PPE in this war against corona virus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Robots are widely suggested to be deployed in different scenarios during the pandemic, to help reduce the infection by performing disinfection, monitoring, delivering, food preparation, and telepresence [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. Robots are also recommended to make intelligent decisions based on the inputs data from the population, which can be analysed through AI [ 17 ].…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…Robots are widely suggested to be deployed in different scenarios during the pandemic, to help reduce the infection by performing disinfection, monitoring, delivering, food preparation, and telepresence [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. Robots are also recommended to make intelligent decisions based on the inputs data from the population, which can be analysed through AI [ 17 ].…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…N95 respirators are a valuable resource, particularly during the COVID-19 pandemic. 19 , 20 However, it has been found that they have a high failure rate. 21 Ideally, a broad range of respirators should fit all users.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Exhaled humidified gases also result in fogging of the eyeglasses, which is a frequent observation of those who wear eyeglasses. 9 , 10 In a recently reported prospective cohort study from India, all users complained of fogging when using PPE and caring for patients with COVID-19. 11 It is a commonly held notion that fogging of eyeglasses indicates poor seal of the N95 respirator and vice versa.…”
Section: Introductionmentioning
confidence: 99%